Exploring Students' Difficulties in Learning English - Astuti, Nuri Fitri; Apsari, Yanuarti (IKIP Siliwangi, 2026)
An international language is a language that is used in any international communication that involves individuals from two or more different nations. The most extensively used language in a variety of global situations is English. English is thus a global language as well as an international language. Therefore, speaking English is not limited to interactions with native English speakers. This study aims to find out the difficulties experienced by high school students in learning English which are based on internal and external factors. The method used in this research is qualitative data. There were thirty students who were selected as respondents of this study. The instruments used were open ended questionnaires and interviews. In this study, it was found that interest and motivation are the keys to the internal problems faced by students in learning english, which then the teacher is an external factor which also the main influences the learning process.